Toxicity of β-(1→3,1→6)-ᴅ-glucans produced by diaporthe sp. endophytes on metarhizium anisopliae (metschnikoff) sorokin assessed by conidia germination speed parameter - Orlandelli, Ravely Casarotti; de ALMEIDA, Tiago Tognolli; Lourenco, Daniela Andressa Lino; Vasconcelos, Ana Flora Dalberto [UNESP]; CORRADI DA SILVA, Maria de Lourdes [UNESP]; de AZEVEDO, João Lúcio; Pamphile, João Alencar (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2020)
We have previously reported that β-(1→3,1→6)-ᴅ-glucans produced by endophytes Diaporthe sp. G27-60 and G65-65 (GenBank accession codes JF766998 and JF767007, respectively) are promising anti-proliferation agents against human breast carcinoma (MCF-7) and hepatocellular carcinoma (HepG2-C3A) cells. However, the literature fails to describe the effects of Diaporthe exopolysaccharides (EPS) on eukaryotic healthy cells. The fungus Metarhizium anisopliae has been employed as model-system to evaluate the toxicity of pharmaceutical and agricultural-interest substances, taking into account, among other parameters, the speed of conidia germination. Current study verified the effect of different concentrations of Diaporthe β-glucans on the germination speed of M. anisopliae. Conidia were incubated with β-glucans treatments (50, 200 and 400 μg/mL) at 28ºC, sampled during 24 h and analyzed by light microscopy. At the end of a 24-h incubation, the amount of germinated conidia reached ≈99% for controls and ranged between 97.7 and 98.6% for treatments. Bayesian analysis indicated that Diaporthe glucans had no toxicity on M. anisopliae and the curve of germination occurred as expected for this fungal strain. Considering the validity of filamentous fungi as model-systems, results are important data on the toxicity of endophytic EPS on healthy cells and may be associated with our previous results obtained for these polymers against tumor cells.
Toxicidade de β-(1→ 3,1→ 6)-ᴅ-glucanas produzidas por endófitos diaporthe sp. sobre metarhizium anisopliae (metschnikoff) sorokin avaliada pelo parâmetro de velocidade de germinação dos conídios
Keywords: Bayesian analysis; Endophytic fungi; Exopolysaccharide; Fungal model-system